Breakage–reflocculation implemented by two-stage shear for enhancing waste-activated sludge dewaterability: Effects of shear condition and extracellular polymeric substances. Issue 4 (12th March 2018) - He, Junguo; Pang, Heliang; Zheng, Yanshi; Jiang, Tao; Xin, Zhiyuan; Zhang, Pengfei; Zhang, Peng
ABSTRACT: The conditioning of waste-activated sludge (WAS) before dewatering is crucial for enhancing sludge dewaterability. The breakage–reflocculation that was implemented by two-stage shear (drastic first-stage shear for breakage and moderate second-stage shear for reflocculation utilizing the bioflocculation function) which was proposed as a novel WAS conditioning method with several advantages (simple operation, lower cost, and none added reagent) compared to traditional methods. Effects of the shear condition and extracellular polymeric substances (EPS) on breakage–reflocculation were orderly investigated. Two equations were developed by response surface methodology for predicting breakage–reflocculation conditioning performance. Analysis of variance (ANOVA) indicated that individual effects of first-stage shear rate ( G 1 ), second-stage shear rate ( G 2 ), second-stage shear time ( t 2 ), and interactive effect of G 1 G 2 were significant. More compact WAS flocs with better dewaterability and larger floc size formed through breakage–reflocculation. This was reflected in that the capillary suction time decreased by 16.9% and mean floc size increased by 24% under the optimum shear condition. In addition, the loosely bound EPS was revealed to be closely negatively correlated with breakage–reflocculation conditioning performance, indicating its adverse role in breakage–reflocculation. The breakage–reflocculation could be used as an independent conditioning method with low cost or a part of combined method.